2018
DOI: 10.1038/s41370-018-0049-6
|View full text |Cite
|
Sign up to set email alerts
|

Flame retardant exposure assessment: findings from a behavioral intervention study

Abstract: Exposure to individual flame retardants was reduced by about half, in some cases, by 1 week of increased hand washing, house cleaning to reduce dust, or combined activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Limited experimental studies suggest that select OPEs are quickly metabolized and excreted in urine with half-lives of several hours ( Burka et al 1991 ; Carignan et al 2016 ; Lynn et al 1981 ; Nomeir et al 1981 ). Studies examining temporal variability of OPE urinary biomarkers ( Supplemental Material , Table S8), including DPHP, BCDPP, and BCEP have generally reported moderate to strong intraclass correlation coefficients (ICC = 0.50–0.81) among pregnant women and non-pregnant adults in repeated urine samples collected within about 1 week up to 12 months ( Cequier et al 2015 ; Gibson et al 2018 ; Hoffman et al 2015 , 2014 ; Meeker et al 2013 ; Romano et al 2017 ). However, some studies have reported poor agreement across multiple urine measurements for some OPE bio-markers.…”
Section: Discussionmentioning
confidence: 99%
“…Limited experimental studies suggest that select OPEs are quickly metabolized and excreted in urine with half-lives of several hours ( Burka et al 1991 ; Carignan et al 2016 ; Lynn et al 1981 ; Nomeir et al 1981 ). Studies examining temporal variability of OPE urinary biomarkers ( Supplemental Material , Table S8), including DPHP, BCDPP, and BCEP have generally reported moderate to strong intraclass correlation coefficients (ICC = 0.50–0.81) among pregnant women and non-pregnant adults in repeated urine samples collected within about 1 week up to 12 months ( Cequier et al 2015 ; Gibson et al 2018 ; Hoffman et al 2015 , 2014 ; Meeker et al 2013 ; Romano et al 2017 ). However, some studies have reported poor agreement across multiple urine measurements for some OPE bio-markers.…”
Section: Discussionmentioning
confidence: 99%
“…While this analysis evaluated differences between maternal and child flame retardant exposure, it is important to remember that these observations were made within the context of a behavioral intervention study designed to reduce exposure (Gibson et al, 2018). Because our assessment of differences between OPE levels in mothers and children was conducted on baseline measurements, the intervention's effectiveness cannot affect our interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…We selected 32 mother and child dyads from a previously established cohort to participate in a study to assess flame retardant levels at three time points (Cowell et al, 2017) within a behavioral intervention trial (Gibson et al, 2018). Families were selected from the Sibling-Hermanos cohort (N = 125), which began in 2008, consisting of Dominican and African-American mothers and children from Northern Manhattan and the South Bronx.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flame retardants (FRs) are anthropogenic chemicals or mixtures of chemicals widely used in commercial and consumer products such as building materials, automobiles, plastics, textiles, furniture, mobile phones, and toys since the 1960s to reduce the flammability and risk of fire [ 21 , 22 , 23 ]. The production and use of FRs are steadily increasing globally; in 2008, global production and use were 1.95 million tons, which increased to 2.62 million tons in 2014 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%